2020
DOI: 10.1007/s00270-020-02436-2
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Outcomes and Predictors of Transarterial Embolization for Type II Endoleak After Endovascular Abdominal Aortic Aneurysm Repair

Abstract: To evaluate the mid-term outcomes of transarterial embolization (TAE) for type II endoleak after endovascular abdominal aortic aneurysm repair (EVAR) and investigate the predictors of sac enlargement after embolization. Materials and Methods:We conducted a retrospective analysis of 55 patients (48 men and 7 women, median age 79.0 (interquartile ranges 74-82) years) who underwent TAE for type II endoleak from 2010 to 2018. The aneurysmal sac enlargement, endoleaks, aneurysm-related adverse event rate, and reint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The embolization results published for NBCA without/with coils in T2ELs [21][22][23]44] tend to be inferior to the EVOH data. Horinouchi et al currently report clinical success rates with NBCH and coils of 73 % and 32 % after 1 or 3 years, respectively [22].…”
Section: Technical and Clinical Results Achieved With Evohmentioning
confidence: 66%
See 1 more Smart Citation
“…The embolization results published for NBCA without/with coils in T2ELs [21][22][23]44] tend to be inferior to the EVOH data. Horinouchi et al currently report clinical success rates with NBCH and coils of 73 % and 32 % after 1 or 3 years, respectively [22].…”
Section: Technical and Clinical Results Achieved With Evohmentioning
confidence: 66%
“…There are two established ways of accessing the endoleak cavity: transarterial catheterization with a microcatheter and percutaneous direct puncture of the aneurysm sac. Performing T2EL coil embolization alone is often ineffective due to the high recanalization rates [20][21][22]. The liquid embolic agents used most frequently in T2ELs are N-butylcyanoacrylate (NBCA) and ethylene vinyl alcohol copolymer (EVOH).…”
Section: Introductionmentioning
confidence: 99%
“…Fujimura et al [23] reported that transarterial embolization of isolated T2ELs with sac expansion using a triaxial system resulted in only a 12.5% resolution of T2ELs at 16 months. Neither of the two reports [23,43] was satisfactory in terms of the outcome of reintervention for T2ELs.…”
Section: Treatment Outcomes For T2els (Conservative/intervention/surgmentioning
confidence: 83%
“…Two reports in East-Asian populations from Japan [23,43] also mentioned a high probability of sac diameter enlargement after treatment for T2ELs. Horinouchi et al [43] suggested that transcatheter arterial embolization for T2ELs should be performed before the sac enlarges to > 10 mm, although this protocol differs from the ESVS guideline recommendations, because the progress of sac diameter enlargement after treatment for T2ELs was significantly associated with a sac diameter of ! 55 mm at the time of the initial intervention for T2ELs.…”
Section: Treatment Outcomes For T2els (Conservative/intervention/surgmentioning
confidence: 96%
See 1 more Smart Citation